A systematic approach to the activities of a regional football federation (using the example of Krasnoyarsk Krai) - Sazontov M.D. ,; Ponomarev V.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop an algorithm for designing a systematic approach to the activities of a regional football federation (using the Krasnoyarsk Krai as an example) and to recommend its implementation in practice. Methods and structure of the study. The study was conducted at the Krasnoyarsk Regional Football Federation between 2022 and 2024. The following research methods were selected to ensure the correct organization and implementation of scientific and theoretical work: analysis of scientific and methodological literature on the topic; questionnaires; interviews, observation, modelling; systematization; abstraction; testing, expert assessment, mathematical statistics, etc. In the process of collecting factual material, 150 coaches and specialists involved in the development of football in the region, as well as more than 800 children and young people who are systematically involved in football, were involved. All this contributed to identifying the overall level of activity of the regional federation and designing a systematic approach to improving the functioning of regional football. Results and conclusions. The theoretical research conducted contributed to the development of an algorithm for designing a systematic approach to the activities of a regional football federation, as well as a systematic analysis of the federation's functioning; an experimental structure and content of a model for improving the activities of the existing regional football federation, based on taking into account the current requirements for the development of the football industry in the region, Russia and in global practice.